Dentists' Perceptions of Mandatory Vaccination for Hepatitis B, Influenza, Measles, and Rubella: A Study in Georgia - Zurab Alkhanishvili; Ketevan Kiguradze-Gogilashvili; Tinatin Svanishvili; Nino Gogichadze; Aleksandre Chkhikvishvili; Sopio Gvazava (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: Healthcare workers, including dentists, are at risk of contracting and transmitting infectious diseases despite the availability of vaccines and clear guidelines on preventive measures. In Georgia, hepatitis B, influenza, measles, and rubella are mandatory preventive immunizations for medical personnel employed in dental clinics.Material and methods: This cross-sectional study aimed to explore the knowledge and attitudes of dentists towards vaccination against these diseases. A questionnaire was administered to a selective group of 165 dentists randomly selected from the 2,435 certified dentists with active status in Georgia.Results: The study found that while most dentists were aware of the mandatory vaccines, there were knowledge gaps regarding the potential severe complications of these diseases and the effectiveness of vaccination. Most dentists had positive attitudes towards vaccination, but a significant proportion reported concerns about the safety and efficacy of vaccines.Conclusions: The study highlights the need for continuing education and awareness-raising initiatives among dentists regarding the importance of vaccination against infectious diseases, which could inform future policies and educational programs in dentistry, with the ultimate goal of reducing the transmission of infectious diseases among healthcare workers and patients.